Markers of Human Creaturehood Soil, Spirit and Salvation - Peters, Ted 1941- (2018)
When faced with the invitation for self-transformation through bio-nano-technology, we must pause to ask: just what does it mean to be a human being? Both scripture and evolution make the same point: we humans live at the metaxy, in the tension between soil and spirit. Genesis 2:7 says we live at the in-between where the ineffable God beyond touches the mundane realm of daily existence. Even in salvation, we will be redeemed creatures and not gods. The promise of technological utopianism, then, becomes an empty promise. Even with dramatic bio-enhancements or improved intelligence, we Homo sapiens must still pray that divine grace will provide the ultimate transformation. In the meantime, we should simply enjoy the metaxy.
Keywords: EVOLUTIONARY theories; Genesis 2:7; Salvation; Spirit; Theology; Transhumanism; Transhumanism; Dignity; Human; metaxy; Spirit; Technology